Badan Amil Zakat Nasional Strategy in Utilizing Digital Platforms During the Covid-19 Pandemic - Gunawan, Sonia Tiara; Kurnia, Tuti; Munawar, Wildan (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
The digital platforms owned by BAZNAS are very varied. Still, the community has yet to fully utilize these platforms, especially during the Covid-19 pandemic when all activities have shifted online. Hence, the collection of zakat digital still needs to be improved compared to the collection of zakat directly. This study aims to find BAZNAS strategies for utilizing digital platforms so that it is expected to increase the collection of zakat funds through digital platforms. This type of research is descriptive qualitative using SWOT analysis techniques. The results of this study indicate that the BAZNAS strategy for utilizing digital platforms to increase the collection of zakat funds amid the Covid-19 pandemic is to develop the six BAZNAS platforms amidst the increasing number of internet users by utilizing online-based advertising and relying on well-known influencers as BAZNAS ambassadors and preparing reliable, accurate, transparent and accountable financial reports.